Ileocecal intussusception in an adult: A case report - Ji Hye KIM,; Kyoung Mi LEE,; Sung Hyun YUN,; Hoon KIM,; Jun Sig KIM,; Min Young YUN,; Seung Baik HAN, (Turkish Journal of Gastroenterology, 2019)
-